Establishment of a bovine in vitro embryo production system for research model experiments - methodology - Nagy, Katalin; Tokár, Alexandra; Sándorová, Lilla; Gócza, Elen; Zomborszky, Zoltán; Stéger, Viktor; Szabari, Miklós; Póti, Péter; Bodó, Szilárd (Animal welfare, Ethology and Housing Systems (AWETH), 2025)
Thanks to 40 years of uninterrupted development, in vitro embryo production (IVEP) plays an increasingly important role in cattle breeding worldwide. Advances in oocyte retrieval, fertilisation in the laboratory, embryo culture, cryopreservation and the laboratory environment have enabled millions of genetically valuable embryos to be produced. In addition to its practical applications, in vitro embryo production (IVEP) provides a basic model environment for a wide range of research. It can be used to model the early gestation period and to study the environmental factors of embryo development, thus answering questions that concern both scientists and practitioners. The design of an embryo production system that delivers reliable results requires the optimisation of many technological steps. Over the past year, the authors have succeeded in developing a well-functioning system for successful bovine embryo production, making it suitable for educational and research purposes. In this communication, the authors describe the development of the system from its inception, its successes and difficulties, and report on the success of the 31 IVEP programmes. On average, 69% of fertilized oocytes cleave and 23.4% develop to an implantable blastocyst, making the system suitable for ovum pick-up (OPU) IVEP programmes.